INTERFERENCE OF SAMBAS MALAY IN PRONOUNCING ENGLISH CONSONANT SOUNDS - Puspita, .; ., Sudarsono; Susilawati, Endang (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract: The aim of this research is to describe how Sambas Malay-speaking students pronounce the English consonant sounds and aspirated sounds. This study particularly focused on the consonant which are not found in Sambas Malay sound system. They consist of consonant fricative sounds [f], [v], [q], [ð], [ʃ], [ʒ], and aspirated sounds [ph], [th], and [kh]. In doing this research, the researcher used an error analysis. The data of this research was collected by asking the students to read sentences provided. In collecting the data, the researcher used a pronunciation test as the main data and interview as supporting data. The total items for pronunciation test are 35 sentences. The participants of this research are 7 Sambas Malay students in the 3rd semester of English language education study program in academic year 2015/2016. The findings of this research show that the pronunciation of Sambas Malay-speaking students is affected by the phonological gap between their L1 and L2, the influence of spelling on pronunciation, their previous learning language rather than their L1, and the role of previous English language teaching. Keywords : Sambas Malay, Error Analysis, Pronunciation Abstrak: Penelitian ini bertujuan untuk mendeskripsikan bagaimana mahasiswa Melayu Sambas mengucapkan bunyi konsonan dan aspirated sounds yang terdapat pada system bunyi Bahasa Inggris. Penelitian ini berfokus pada konsonan Inggris yang tidak terdapat pada system bunyi Bahasa Melayu. Konsonan-konsonan tersebut terdiri dari bunyi konsonan geseran yaitu [f], [v], [q], [ð], [ʃ], [ʒ], dan aspirated  sounds [ph], [th], and [kh]. Dalam melakukan penelitian ini, penulis menggunakan metode error analysis. Data dalam penelitian ini dikumpulkan dengan meminta mahasiswa untuk membaca kalimat-kalimat yang telah disediakan. Dalam mengumpulkan data, penulis menggunakan tes pengucapan sebagai data utama dan wawancara sebagai data pendukung. Terdapat 35 kalimat untuk tes pengucapan. Peserta penelitian ini adalah  7 mahasiswa Melayu Sambas yang berada di semester 3 jurusan Bahasa Inggris, Fakultas Keguruan dan Ilmu Pendidikan tahun akademik 2015/2016. Hasil dari penelitian ini menunjukkan bahwa pengucapan mahasiswa Melayu Sambas dipengaruhi oleh perbedaan fonologi antara bahasa ibu dan bahasa asing, ejaan pada pengucapan, bahasa yang telah mereka pelajari sebelumnya selain bahasa ibu, dan peran dari pengajaran bahasa Inggris sebelumnya. Kata kunci : Melayu Sambas, Error Analysis, Pengucapan.